Masa Depan dan Pengembangan Bioetanol di Indonesia - Khabibulloh, Mohammad J M; Suhartatik, Nanik; Mustofa, Akhmad (AGRITEKNO: Jurnal Teknologi Pertanian, 2024)
Bioethanol plays a crucial role in Indonesia’s development, given its wide application across various industries, such as food, chemicals, pharmaceuticals, cosmetics, and alternative fuel. The diversity of feedstocks available for bioethanol production ranging from food crops, lignocellulose, food waste, to microalgae reflects positive advancements in production technologies. This study examines several aspects of bioethanol, including its historical development, the specifications applied in Indonesia, feedstock types, and the current demand for bioethanol in the country. The primary aim of this research is to identify the most promising feedstocks for large-scale bioethanol production in Indonesia. The methodology employed is a narrative literature review, drawing from 37 journal articles, 8 thesis documents, 7 web articles, and 2 publications from Badan Statistik Nasional. The analysis identifies the best feedstocks for bioethanol production in Indonesia, highlighting macroalgae, microalgae, and food waste as having significant potential to support the sustainable growth of the bioethanol industry in the future.